Analysis of the genomic landscape of yolk sac tumors reveals mechanisms of evolution and chemoresistance - Xuan Zong (Nature Portfolio, 2021)
Yolk sac tumours are a type of ovarian germ cell tumours. Here, the authors perform exome and RNA sequencing of clinical samples of 30 patients, characterize the mutational landscape of these rare tumours, and identify molecular features associated with resistance to cisplatin-based therapies.